Céli Dé in Ireland: monastic writing and identity in the early Middle Ages - Follett, Westley (Boydell & Brewer, 2006)
A detailed investigation into the mysterious group of monks, the CeÌli DeÌ, who flourished in early medieval Ireland. The CeÌli DeÌ (`clients of God'), sometimes referred to as the Culdees, comprise the group of monks who first appeared in Ireland in the eighth century in association with St MaÌel Ruain of Tallaght. Although influential and important in the development of the monastic tradition in Ireland, they have been neglected in general histories. This book offers an investigation into the movement. Proceeding from an examination of ascetic practice and theory in early medieval Ireland, followed by a fresh look at the evidence most often cited in support of the prevailing theory of ́„—‘ceÌli DeÌ́„—’ identity, the author challenges the orthodox opinion that they were an order or movement intent upon monastic reform at a time of declining religious discipline. At the heart of the book is a manuscript-centred critical evaluation of the large corpus of putative ́„—‘ceÌli DeÌ́„—’ texts, offered as a means for establishing a more comprehensive assessment of who and what ́„—‘ceÌli DeÌ́„—’ were. Dr Follett argues that they are properly understood as the self-identified members of the personal retinue of God, in whose service they distinguished themselves from other monks and monastic communities in their personal devotion, pastoral care, Sunday observance, and other matters. A catalogue of ́„—‘ceÌli DeÌ́„—’ texts with manuscript references is provided in an appendix. WESTLEY FOLLETT is Assistant Professor of History at the University of Southern Mississippi.